THE FUTURE OF WORK: brief theoretical review of the debate among contemporaries - Sanson, Cesar (Universidade de Brasília, 2021)
Theorists of the work world identify three ongoing changes that have been changing the labor society: the evolution of productive forces, the financialization and the weakening of the State as a regulator of the asymmetry between capital and work. There is a growing perception that the wage society can no longer include everyone. Are there alternatives to wage as a mechanism of social inclusion?